Experimental Investigations of Actuators Based on Carbon Nanotube Architectures - Geier, Sebastian; Mahrholz, Thorsten; Wierach, Peter; Sinapius, Michael (Smart Structures and Materials, 2017)
Commercially successful actuators typically meet a mechanical profile which combines high flexibility and stiffness. Current smart materials used as electromechanical actuators suffer from low or unstable mechanical properties. This is the reason why these actuators are additionally fixed on structures. This kind of actuators represents an additional weight when they are switched off. A new class of carbon nanotube actuators shows promising electromechanical properties combining low density, high Young’s modulus and comparatively high free strains up to 1% $$%$$ . Paper-like architectures made of carbon nanotubes are tested in capacitor mode—two electrodes are immersed into an electrolyte. As a result an in-plane deflection of the electrodes can be detected. The actuation-mechanism is still subject of controversy. Different experiments indicate different physical effects. A comparison of the results reveals a possible dependency on the specimen-composition. Actuated tensile tests are carried out addressing the dependencies between specimen composition and possible physical effects. Two architectures are tested and compared: papers made of randomly oriented single-walled carbon nanotubes and multi-walled carbon nanotube-arrays, which feature single, continuous carbon nanotubes in one dimension of the specimen. The tests are conducted in dry, wet and wet/actuated condition to determine further effects of swelling and mechanical weakening. Different actuation potentials and electrolytes are tested. The mechanical performance of the carbon nanotube paper strongly depends on the conditions, which is demonstrated by a significant reduction of the Young’s modulus. Additionally, electrical charging seems to start an irreversible mechanical degradation. A general statement for CNT-arrays cannot be easily given because of the variation in the results. If the best results are considered to be the ideal results, no condition dependency can be detected. According to the experimental set-up, the sample composition and the testing method a quantum-mechanical effect might be most likely the reason for the array-actuation.